MEMBER APPLICATION FKMI DISPLAYING DATA (ISLAMIC STUDENTS FORUM COMMUNICATIONS) USING THE CONTROLS IN VISUAL BASIC 6.0 TREEVIEW - Achmad Dwi Saputro; Yuliana Yuliana, Skom, MMSi (Jurnal Sistem Informasi, 2004)
At this time, especially in Indonesia, in connection with the reform era and on behalfof democracy, the more established organizations, including the student organizationthat calls itself FKMI or abbreviation Communication Forum of Islamic Students,which turned out to interest students and female college students interested inbecoming a member FKMI this quite often because of their interest in the activitiesoffered by FKMI.A student can become a member by registering directly or through Volentirkesekretariat here is someone who has become a member and active in all FKMIFKMI activities and have the right to recruit as many people to join become amember.FKMI offers to its members than to know each other more with students from othercampuses, they can also get additional knowledge about the religion of Islam, Scienceand Technology (Science and Technology), law, politics, literature and others byasking them an expert in his field when FKMI seminar is being held.In improving its existence as an organization, we need a good application programs toprocess data processing becomes faster and better.